Comparison of separate and intermittent heat and cold therapy in labour pain management - Marjan Ahmad-Shirvani; Jila Ganji (Tehran University of Medical Sciences, 2016)
Background & Aim: Although cold and heat have been recommended for labor pain relief, comparison of them and intermittent change in cold and heat therapy has been less considered. This study compared the effects of separate and intermittent heat and cold on labor pain relief and some birth outcomes. Methods & Materials: This was a randomized clinical trial. Ninety-six parturient women were randomly allocated to three groups. The heat therapy group received warm water bags and the cold therapy group received ice bags over abdomen, lower abdomen and low back, intermittently based on mother's preference, in the first stage and also over perineum in the second stage of labor. In the intermitted heat and cold group, a warm water bag was used followed by an ice bag during the active phase, and the second stage. Pain severity was assessed by a visual analogue scale. Duration of labor, mothers' satisfaction and fetal and neonatal outcomes were assessed. Mean, standard deviation, frequency, Chi-square, ANOVA and repeated measurement were used for data analysis. Results: Although pain intensity was slightly lower in the heat therapy group during labor, it was not significantly different between three groups. The duration of the second stage was significantly lower in the cold therapy group (p=0.02), There were not significant differences in duration of the first and third stages, fetal heart rate and Apgar score between the groups. Mothers' satisfaction was high in 56.2% of the heat and the intermittent heat and cold therapy groups compared to 37.5% in the cold therapy group (p>0.05). Conclusion: To provide pain relief during labour, application of heat and cold, either separate or intermittent can be used based on the mother's preference.